Nasionalisme Religius dalam Film-Film Amerika dan Indonesia - Herman Felani; Ida Rochani Adi (Jurnal Komunikasi)
This study aimed to examine religion-based nationalism in popular American and Indonesian films. The subjects of this research were American and Indonesian films from 1915-2020. This research used a mixed qualitative and quantitative research with content analysis approach. The findings of this study indicated that the discourse of religious nationalism was constructed in popular American and Indonesian films to carry out the practice of inclusion and exclusion of certain groups. The results of the analysis showed that religious nationalism in American films was dominated by Christian nationalism, while religious nationalism in Indonesian films was dominated by discourses of Islamic nationalism. Both American and Indonesian films were against the ideology of communism, but American films were dominated by exclusive nationalism, while Indonesian films were mostly inclusive. American films also tended to show Islamophobia while Indonesian films positioned Islam more as a spirit of religious nationalism. This research has theoretical implications for increasing studies on nationalism which always appears and strengthens in films as a form of mass communication.